How do internal factors impact career adaptability of undergraduate Papua students? - Agoes Salim, Rose Mini (Universitas Muhammadiyah Surakarta, 2021)
Abstract. The data from this study show that students from the region of Papua tend to have difficulty adapting to lectures, have low graduation rates, have difficulty attending lectures, and so on, indicating a low likelihood of career adaptability. The distinctive characteristics of Papuan people result in many of them conforming to social influences, such as friendships while prioritizing friendships over academics. On the other hand, students from the region of Papua who excelled at the lecture may have an intrinsicunderlying value to their success. Therefore, this study aims to analyze the career adaptability of Papuan students as influenced by core self-evaluation (CSE) and perceived peer support (PPS) as internal factors. The respondents of this study were 176 Papuan undergraduate students enrolled in universities throughout Papua and other provinces in Indonesia. The instruments of this study, which were distributed online, included the Social Provision Scale, the Core Self-Evaluation Scale, and the Career Adaptability Scale.Data processing was carried out by using multiple regression with stepwise method. The results show that CSE and PPS significantly contribute to the career adaptability of Papuan students in tertiary institutions. These results are expected to provide insight into the significance of developing a positive core self-evaluation and perceptions of peer support to increase career adaptability. The limitation is in online data collection, which limits feedback if some items are not understood. In addition, it is not possible to determine the seriousness of the respondents when filling out the questionnaire. The average respondents already have fairly good CSE indicating fairly good educational orientation, which is different from thegeneral phenomenon observed in other Papuan students.Keywords: career adaptability; core self-evaluation; perceived peer support; Papuan undergraduate students.